Building Energy Simulation Model Application to Greenhouse Microclimate, Covering Material and Thermal Blanket Modelling: A Review (2022)
This review documents the present knowledge and knowledge gap in applying building energy simulation (BES) dynamic models to greenhouses. The focus of this review is to compile the literature on the BES dynamic model of greenhouse microclimate, covering materials, energy requirements and thermal blankets using the Transient System Simulation version 18 (TRNSYS 18) software. Fifty-two journal articles, mostly Science Citation Index (SCI) and Scopus index journals, on BES development and simulation of greenhouse microclimate, greenhouse energy requirement, covering materials and thermal blankets were reviewed. These researchers sought to optimise greenhouse crop production. The main features of the TRNSYS 18 software for BES development are outlined; each research consulted for this review successfully developed, simulated and validated its BES. However, none of these developed models included the vapour pressure deficit (VPD) as a greenhouse microclimate factor, an essential climate parameter. In conclusion, this study demonstrates that applying a BES developed using TRNSYS has excellent potential to optimise greenhouse crop production and help adapt appropriate climate control strategies and energysaving techniques. However, it is recommended to include VPD in future BES model development